Estado da arte e perspectivas sobre a produção científica relacionados aos pseudoescorpiões - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Scientometrics is one of the methods used to evaluate, in a qualitative and / or quantitative way, the scientific production on a certain subject. Researches on this approach have increased in last decades. Biodiversity, its distribution, conservation and its knowledge are plausible subjects of investigation and analysis of its phenomena. In this view, the present study adopted the scientific knowledge produced about studies involving pseudoscorpions. Scientometry is a methodological option to evaluate knowledge about a particular topic. Thus, we used scientometric procedures for the development of this study, being composed of two parts. The first chapter dealt with the conceptualization of the scientometric method and its importance. The second chapter was based on a survey and analysis of scientific production related to pseudoscorpions, investigating the authors who published in the period from 1945 to 2017, the countries that produced the most, the periodicals that published about the group and how much was studied within the large areas. Therefore, such research becomes important and necessary in order to contribute to the diagnosis of the research trends involving this taxonomic group
Keywords: Cienciometria; Tendências de pesquisas; Lacunas de conhecimento; Arachnida; Scientometrics; Search Trends; Gaps in knowledge; Arachnida; CIENCIAS BIOLOGICAS